Myocardial Perfusion Imaging in the Evaluation of Outcome of Coronary Intervention in Coronary Artery Disease Patients - Majumder, Sanhita; Begum, Shamim Momtaz Ferdousi; Paul, Ankan Kumar; Singha, Chayan (Bangladesh Journal of Nuclear Medicine, 2019)
Background: Coronary artery disease (CAD) is an important medical and public health issue because it is one of the leading causes of death and disability throughout the world and is rapidly emerging as a major cause of mortality in developing countries including Bangladesh. SPECT-MPI is a cost- effective and non invasive means of identifying ischemic and viable myocardium along with its vascular distribution. This study is aimed to evaluate prospectively the ability of MPI to predict the outcome of Coronary Intervention in CAD patients of Bangladesh who are referred to National Institute of Nuclear Medicine & Allied Sciences (NINMAS) for performing MPI. Patients and Methods: This prospective longitudinal and observational type of study was carried out in National Institute of Nuclear Medicine & Allied Sciences (NINMAS) located at Bangabandhu Sheikh Mujib Medical University (BSMMU) campus, from July 2017 to June 2018with 12 CAD patients who were referred here. Gated SPECT MPI was performed on the selected patients before any coronary intervention to predict myocardial viability & probable outcome of intervention. A follow up MPI of the same patients was performed after minimum 3 to 4 months of revascularization procedure to determine the outcome of intervention and to detect in stent restenosis or new onset ischemia if present which can be prevented by additional revascularization procedure. Finally pre and post intervention MPI results were analyzed by standard statistical analysis by using the Statistical Package for Social Sciences version 20.0 for Windows (SPSS Inc., Chicago, Illinois, USA). P values <0.05 was considered as statistically significant. Results: The sensitivity of MPI for the initial evaluation and risk stratification by diagnosing perfusion defect in the enrolled 12 CAD patients have been found to be 90%,77.8% and 81.8% in case of LAD, LCX and RCA territories respectively. Whereas the specificity and positive predictive value have been found 100% for LAD and RCA territories. About 16.67% patients were found to have restenosis in this study diagnosed by early post-intervention MPI. It was observed that majority of the patients had perfusion defect in LAD territory. 3(25.0%) patients had fixed defect, 5(41.7%) patients had partial reversible defect and 4(33.3%) patients had complete reversible defect in pre intervention MPI. In post intervention MPI, 4(33.3%) patients had partially reversible perfusion defect, 2(16.7%) patients had fixed perfusion defect, 1(3.3%) patient was found with completely reversible perfusion defect and 5(41.7%) patients had normal MPI findings. The result was found statistically significant (P value <0.05) in case of partially reversible perfusion defect and normal MPI findings when before and after intervention MPI results were compared. The difference of mean percentage of involved myocardium by fixed defect between pre and post intervention MPI was found statistically significant (P<0.05) in case of LAD territory and total LV myocardium involvement. 33.3% patients were in high risk before undergoing intervention, whereas it was found to be 25% after intervention which was calculated on the basis of their pre and post intervention SSS(Summed Stress Score) result. Conclusion: The results of this study have indicated that SPECT MPI provides significant independent information concerning the outcome of coronary intervention in CAD patients. Furthermore, early SPECT MPI after intervention successfully identified significant improvement of myocardial viability after revascularization in patients having complete or reversible perfusion defects found in pre intervention MPI along with identifying those having restenosis. It could also depict the reduction of percentage of myocardial fixed defects within 3-4 months after intervention which is also a positive outcome of coronary revascularization. Bangladesh J. Nuclear Med. 22(1): 23-29, Jan 2019